Quality evaluation through self-assessment: a novel method to gain insight into ERCP performance - Ekkelenkamp, Vivian E (BMJ Publishing Group, 2014)
BACKGROUND: The American Society for Gastrointestinal Endoscopy Committee on Outcomes Research has recommended monitoring nine endoscopic retrograde cholangiopancreatography (ERCP)-specific quality indicators for quality assurance in ERCP. With the development of a self-assessment tool for ERCP (Rotterdam Assessment Form for ERCP—RAF-E), key indicators can easily be assessed. OBJECTIVE: The aim of this study was to test in daily practice an easy-to-use form for assessment of procedural quality in ERCP and to determine ERCP quality outcomes in a tertiary referral hospital. DESIGN: This was a prospective study carried out in a tertiary referral hospital. In January 2008, a quality self-assessment programme was started. Five qualified endoscopists participated in this study. All ERCPs were appraised using RAF-E. Primary parameters were common bile duct (CBD) cannulation rate and procedural success. The indication was classified and procedural difficulty was graded; success rates of therapeutic interventions were measured for all different difficulty degrees. RESULTS: A total number of 1691 ERCPs were performed. 1515 (89.6%) of these were appraised using RAF-E. Median CBD cannulation success rate was 94.1%. Successful sphincterotomy was accomplished in almost all patients (median 100%; range 98.2–100%). Stent placement was successful in 97.8% and complete stone extraction, if indicated, was achieved in 86.8%. CONCLUSIONS: Quality indicators for ERCP can be measured using the Rotterdam self-assessment programme for ERCP. Outcome data in ERCPs obtained with this RAF-E provide insight into the quality of individual as well as group performance and can be used to assess and set standards for quality control in ERCP.